The Effect of Flipped-Problem Based Learning on Curiosity, Creative Thinking and Problem-Solving Ability in Environmental Change Substance - Astri Suhartini; Aditya Marianti (Universitas Negeri Semarang, 2023)
The purpose of this study was to analyze the effect of the Flipped-Problem Based Learning model on curiosity, creative thinking skills and problem solving, and to analyze the relationship between these variables. The study was Pre-Experimental using One Group Posttest Design and One Group Pretest-Posttest Design. The research sample was students of class X-5, X-8 and X-9 at SMA N 3 Salatiga who were selected by purposive sampling. Questionnaires, assessment reports and test instruments are used as data collection tools. The results of this study are students' curiosity in the three experimental classes with high and moderate criteria reaching > 50%. Classical completeness in creative thinking ability reaches > 70% and the n-gain in problem solving ability is in moderate criteria. The relationship between variables has a simultaneous and partial pattern. From the results of the study, it can be concluded that the Flipped-Problem Based Learning model influences curiosity, creative thinking and problem solving as well as the relationship pattern of the variables are partial and simultaneous patterns.